ANALISIS RISIKO KESELAMATAN PEKERJA PT. DAISY MUTIARA SAMUDRA DI DERMAGA 101 DENGAN MENGGUNAKAN METODE HIRARC - Kencana Verawati; Nurul Falah (Universitas Negeri Jakarta, 2021)
Analysis of the safety risks of PT. Daisy Mutiara Samudra at Dermaga 101 using the HIRARC method, HIRARC is a tool or method for identifying, assessing and controlling hazards based on activities in each workplace. The results of hazard identification carried out in 3 places on the pier 101 - 102, there are 14 hazards related to safety workers. From the results of identification of the hazard factors, there are 3 factors, namely food factors, facilities factors, human factors. Based on the results of the risk assessment, it is known that the highest percentage of risk level at wharf 101 is moderate risk, which is 58%. So that the recommendation given by the author to overcome these risks is the addition of facilities and improvement of the worker management system.